Text analysis of rehabilitation nursing policy in China from the perspective of policy tools - Li, Wenjia; Zhu, Yuhan; Zhu, Xuehua (Frontiers in Public Health, 2025)
ObjectiveThis study aims to analyze the specific content and structural characteristics of rehabilitation nursing-related policies in China from 2007 to 2024, utilizing the perspective of policy tools. The goal is to provide insights for the subsequent optimization and enhancement of the rehabilitation nursing policy system.MethodsAccording to the classification method of policy instruments proposed by public policy scholars Rothwell and Zegveld, this study identified the X dimension (basic policy instrument) and categorized the included policies into demand-oriented, supply-oriented, and environment-based policies. Simultaneously, in light of multi-level service needs, an analysis of the elements constituting the rehabilitation nursing system was conducted in conjunction with existing research. This led to the summarization of five levels within the rehabilitation nursing system: nursing staff, service objectives, service items, service methods, and safeguard measures. These levels were designated as the Y dimension (service system) for this study. Utilizing this two-dimensional analytical framework, researchers classified and coded relevant policy texts that met established criteria. Subsequently, they analyzed their content and performed a quantitative assessment regarding both quantity and distribution patterns.ResultsA total of 41 policy documents were analyzed, resulting in the extraction of 292 policy terms, and in dimension X, environment-based, supply-based, and demand-based policy instruments comprised 46.58, 36.64, and 16.78%, respectively. In dimension Y, nursing staff, service objectives, service items, service methods, and safeguard measures accounted for 22.95, 12.67, 12.67, 20.89, and 25.00%, respectively. Overall, the rehabilitation nursing policy in China is predominantly characterized by environment-based policy tools, while demand-based policy tools are comparatively underrepresented.ConclusionThe government has increasingly prioritized rehabilitation nursing care; consequently, the current policy framework is evolving toward greater specialization, standardization, and systematization. Nevertheless, there remains a need to optimize the structural application of policy tools further, particularly concerning enhancing the utilization of demand-side policy instruments.